Pregnancy outcomes and mother-to-child transmission rate in HTLV-1/2 infected women attending two public hospitals in the metropolitan area of Rio de Janeiro. - Danielle Bittencourt Sodré Barmpas; Denise Leite Maia Monteiro; Stella Regina Taquette; Nádia Cristina Pinheiro Rodrigues; Alexandre José Baptista Trajano; Juliana de Castro Cunha; Camila Lattanzi Nunes; Lucia Helena Cavalheiro Villela; Sérgio A M Teixeira; Denise Cardoso das Neves Sztajnbok; Márcio Neves Bóia (Public Library of Science (PLoS), 2019)
HTLV-1/2 are transmitted sexually, by whole cell blood products and from mother-to-child (MTC), mainly through breastfeeding. HTLV-1/2 prevalence in pregnant women is high in Rio de Janeiro, however there were no local studies addressing the rate of adverse pregnancy outcomes (APO) and MTC transmission. The aim was to study sociodemographic characteristics which may be associated to HTLV-1/2 infection and describe pregnancy outcomes and MTC transmission in HTLV-1/2-positive women. The cross-sectional study screened 1,628 pregnant women in of Rio de Janeiro (2012-2014) and found 12 asymptomatic carrier mothers (prevalence = 0.74%). Pregnancy outcome information was retrieved from medical records. Sociodemographic characteristics were similar between the positive and negative groups except for maternal age, which was higher in carrier mothers. The incidence of adverse pregnancy outcomes was similar in infected and non-infected patients (p = 0.33), however there was a high rate of premature rupture of membranes (PROM) amid infected mothers (3/12). Multilevel logistic regression found that for each additional year of age, the chance of being HTLV-1/2-positive increased 11% and that having another sexually transmitted infection (STI) increased 9 times the chance of being infected. Carrier mothers had more antenatal visits (OR = 5.26). Among the children of HTLV-1/2-positive mothers there was one fetal death, one infant death and one loss of follow-up. After two years of follow-up there was one case of MTC transmission (1/9). The mother reported breastfeeding for one month only. Knowledge about factors associated to HTLV-1/2 infection, its impact on pregnancy outcomes and the MTC transmission rate is important to guide public health policies on antenatal screening and management.